2008
DOI: 10.1007/s12032-008-9112-9
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer in women: histological type and patient age from 1985 to 2005

Abstract: The aim of the study was to analyse changes in histological type and age of presentation in female lung cancer patients during a period of 20 years. The obtained results are compared with those available from the literature published in various parts of the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
2
0
2
Order By: Relevance
“…World Health Organization, 2007; O' Rourke and Djukic, 2008) and in contrast to a report that showed a high frequency of SCC among Serbian resident women (Stojsic et al, 2009(Stojsic et al, , 2010, we found a relatively higher frequency of adenocarcinoma than SCC among Serbian immigrant women. World Health Organization, 2007; O' Rourke and Djukic, 2008) and in contrast to a report that showed a high frequency of SCC among Serbian resident women (Stojsic et al, 2009(Stojsic et al, , 2010, we found a relatively higher frequency of adenocarcinoma than SCC among Serbian immigrant women.…”
Section: Lung Cancer By Histologycontrasting
confidence: 99%
See 1 more Smart Citation
“…World Health Organization, 2007; O' Rourke and Djukic, 2008) and in contrast to a report that showed a high frequency of SCC among Serbian resident women (Stojsic et al, 2009(Stojsic et al, , 2010, we found a relatively higher frequency of adenocarcinoma than SCC among Serbian immigrant women. World Health Organization, 2007; O' Rourke and Djukic, 2008) and in contrast to a report that showed a high frequency of SCC among Serbian resident women (Stojsic et al, 2009(Stojsic et al, , 2010, we found a relatively higher frequency of adenocarcinoma than SCC among Serbian immigrant women.…”
Section: Lung Cancer By Histologycontrasting
confidence: 99%
“…Our results, in agreement with the report of CI5 and descriptive studies in Serbia (Stojsic et al, 2009(Stojsic et al, , 2010, showed that SCC was the most frequent histology of lung cancer among Serbian men. The prevalence of smoking was high in Serbia in 2000: approximately 46% of Serbian resident men and 31% of women smoked, whereas the prevalence of smoking among Swedish men and women was 17 and 21%, respectively (European health for all statistical database.…”
Section: Lung Cancer By Histologysupporting
confidence: 93%
“…In spite of a high prevalence of smoking among Serbian resident women [26,27] and in contrast with a report that showed a high frequency of SCC among Serbian resident women [24,25], we found a relatively higher frequency of adenocarcinoma than SCC among Serbian immigrant women. Changes in smoking behaviors and tobacco products or integration in the culture of adopted country might be some explanations for the observed difference between Serbian immigrant and resident women in lung cancer rates by histology.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results in agreement with the report of CI5 and descriptive studies in Serbia [24,25], showed that SCC was the most frequent histology of lung cancer among Serbian men ( Table 3). The prevalence of smoking was high in Serbia in 2000: approximately 46% of Serbian resident men and 31% of women smoked, while the prevalence of smoking among Swedish men and women was 17% and 21%, respectively [26].…”
Section: Discussionsupporting
confidence: 93%